A modified plate model for an efficient analytical treatment of stress concentrations at notches. Issue 1 (17th December 2018) - Felger, Julian; Becker, Wilfried
Abstract: In the present work, a modified plate model is proposed lying in‐between the established Kirchhoff‐Love and first‐order shear deformation plate theories. The resulting system of partial differential equations can be solved using a complex potential approach which allows for tackling complex geometries such as sharp or rounded notches. Using the proposed model, the singular stress field in the vicinity of a sharp notch can be obtained explicitly and the influence of the notch opening‐angle on the singular behaviour is investigated. It is shown that resulting bending moments and transverse shear forces match with asymptotic solutions according to first‐order shear deformation plate theory and are in very good agreement with numerical results.